2018
DOI: 10.1007/jhep01(2018)070
|View full text |Cite
|
Sign up to set email alerts
|

Collinear and TMD quark and gluon densities from parton branching solution of QCD evolution equations

Abstract: We study parton-branching solutions of QCD evolution equations and present a method to construct both collinear and transverse momentum dependent (TMD) parton densities from this approach. We work with next-to-leading-order (NLO) accuracy in the strong coupling. Using the unitarity picture in terms of resolvable and non-resolvable branchings, we analyze the role of the soft-gluon resolution scale in the evolution equations. For longitudinal momentum distributions, we find agreement of our numerical calculation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 105 publications
(174 reference statements)
2
152
0
Order By: Relevance
“…In [1,2] we demonstrated that at LO and NLO these PDFs from Parton branching method are within 1% identical with the semi-analytical solution of the DGLAP evolution as implemented in QCDNUM [6]. Such precision was achieved with z m = 1 − 10 −3 and higher z m gives even better agreement.…”
Section: Methods Descriptionmentioning
confidence: 54%
See 4 more Smart Citations
“…In [1,2] we demonstrated that at LO and NLO these PDFs from Parton branching method are within 1% identical with the semi-analytical solution of the DGLAP evolution as implemented in QCDNUM [6]. Such precision was achieved with z m = 1 − 10 −3 and higher z m gives even better agreement.…”
Section: Methods Descriptionmentioning
confidence: 54%
“…Motivated by easy implementation and extensibility and good control over the uncertainties we decided for Monte Carlo technique which employs Markov chain of the branching to solve equation (2.1). Within this method the ∆ a (µ 2 2 )/∆ a (µ 2 1 ) is employed as a non-branching probability between two consequent scales µ 2 1 and µ 2 2 and the splitting function integrated over z < z m represents the branching probability. The method is described in more detail in [2].…”
Section: Methods Descriptionmentioning
confidence: 99%
See 3 more Smart Citations